PERFORMING ARTS AND EMOTIONAL INTELLIGENCE DEVELOPMENT - Damodaran B; Monisha J; Shanthi V; Abhinaya B; Thiruchenduran, Mohana; Yang, Yu (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Emotional intelligence has been a very crucial competency in the development of interpersonal communication, social interaction, and psychological health in the contemporary society. Emotional intelligence can be developed through creative disciplines like music, dance and theatre, which offer strong platforms of emotional expression and experiential learning, and performing arts offer a promising avenue of emotional intelligence development. This paper explores the links between the involvement in performing arts and the growth of emotional intelligence through the theoretical bases, the practice in education, therapeutic implications, and empirically measured by arts-based programs. Performing arts activities involve participants in emotional interpretation, collective performance, and expression of communication and this helps in the improvement of emotional awareness, empathy, and emotional control. Case-based analysis shows quantifiable change in emotional intelligence measures of the participants who have already participated in performing arts programs. The results indicate that the organized participation in performing arts facilitates emotionally oriented learning, through encouragement of self-reflection, socialization and expression of emotions in conducive creative settings. Performing arts can be used by educational institutions and community organizations as useful tools to develop emotionally intelligent individuals with the capability to empathize, collaborate, and develop resilience to emotions. The study cites the need to incorporate arts based practices in the education and development models to enhance comprehensive human development and societal welfare.